Influence of planting methods and organic amendments on rice yield and bacterial communities in the rhizosphere soil - Tang, Zhiqiang; Zhang, Liying; He, Na; Liu, Zhiqi; Ma, Zuobin; Fu, Liang; Wang, Hui; Wang, Changhua; Sui, Guomin; Zheng, Wenjing (Frontiers in Microbiology, 2022)
A comprehensive understanding of rice cultivation techniques and organic amendments affecting soil quality, enzyme activities and bacterial community structure is crucial. We investigated two planting methods (direct seeding and transplanting) of paddy rice (Oryza sativa) and organic amendments with rice straw and biochar on crop yield and soil biological and physicochemical properties. Rhizosphere bacterial communities at the maturity stage of rice growth were characterized through high-throughput 16S rRNA sequencing. Soil biochemical properties and enzyme activity levels were analyzed. Grain yield of paddy rice with transplanting increased 10.6% more than that with direct seeding. The application of rice straw increased grain yield by 7.1 and 8.2%, more than with biochar and the control, respectively. Compared to biochar and the control, the application of rice straw significantly increased sucrase, cellulase, protease, organic carbon, available phosphorus, nitrate, and ammonium. The application of biochar increased microbial biomass nitrogen and carbon, urease, pH, hydrolyzable nitrogen, and available potassium in comparison with the application of rice straw and the control. Principal coordinate analysis and dissimilarity distances confirmed that there were significant differences among the microbial communities associated with planting methods and organic amendments. Bacteroidetes, Nitrospirae, Firmicutes, and Gemmatimonadetes abundance increased with rice straw relative to biochar and the control. The biochar addition was associated with significant increases in Chloroflexi, Patescibacteria, Proteobacteria, and Actinobacteria abundance. Pearson’s correlation analyses showed that bacterial phyla-levels were positively correlated with soil properties, and soil enzyme activity levels were positively correlated with cellulose. Nitrospirae abundance was positively correlated with sucrase, protease, and ammonium. These results suggest that planting methods and organic amendments impact soil biochemical characteristics, enzyme activity levels, and microbial community composition.